Motivating Speaking Skills: First-Semester Chemical Engineering Students’ Perceptions - Laili Inayatus Sholihah; Siti Aisah; Rita Handayani (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2026)
Currently, students often have difficulty speaking English due to a lack of confidence, limited vocabulary, fear of grammar mistakes, and difficulty in pronunciation. The current study investigates the perceptions and motivations of first-semester Chemical Engineering students in using English songs, and whether these songs can improve their speaking skills and can help overcome these challenges. Utilizing a mixed-methods approach, data were collected from 50 first-semester students in Chemical Engineering Study Program at one public university in Banten Province, Indonesia, through questionnaires and interviews. The questionnaire utilized a four-point Likert scale based on their agreement and disagreement. The questionnaire consisted of 16 statements, while the interview consisted of three questions. The findings reveal that English songs significantly contribute to improving pronunciation, vocabulary retention, and confidence in speaking. 80% of students reported being more motivated to speak English through songs. The study concludes that integrating English songs into language instruction offers an effective and enjoyable approach to developing speaking skills, fostering both linguistic competence and motivational engagement. Academically, this study contributes to English language learning by providing evidence on the role of English songs in language acquisition. Practically, this study offers an interesting, inexpensive, effective, and enjoyable method for teachers to improve students' speaking skills.